PROGRAM BERKELANJUTAN MEMBANTU NAGARI MEMBANGUN DI NAGARI SALAYO KECAMATAN KUBUNG KABUPATEN SOLOK - Indah Maya Sari; Denny Yohana (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2021)
Nagari-Owned Enterprises (BUMNag) must be managed professionally to generate profits and contribute to the welfare of the villagers. BUMNag Salayo was established in 2017 but had not run and functioned as it should. The problem faced by BUMNag Salayo is that it does not yet have a competent manager, so activities must be stopped for one year. This activity aims to assist in selecting the Salayo BUMNag operational management by Article 14 of the Permendesa No.14 of 2015. The Nagari government selects the BUMNag operational management, which is decided in the Nagari Deliberation (Musna). The Community Service Team came to Nagari Salayo, Kubung District, Solok Regency has assisted with discussion, counselling, and technical guidance. Assistance has been carried out since the revitalization plan, the election committee's preparation, the election mechanism document, the selection process, and the provision of entrepreneurial knowledge. The results obtained were the operational management of BUMNag, which were decided in the Nagari Deliberation. It is hoped that the elected management can run BUMNag well and complete the required registration documents with the Ministry of Law and Human Rights.